Online Taxy Driver Financial Feasibility Analysis (Case Study Pekanbaru InDriver Motorcycle) - Afdhal Saputra, Riski; Taufik, Hendra; Sebayang, Mardani (Jurnal Teknologi dan Rekayasa Sipil, 2023)
Started from a group in a social network called Vkontakte, InDriver now has become international level information and technology company in online transport field. InDriver Entered Indonesia in 2019, and present in Pekanbaru in early 2020. InDriver accomodates the workers to become drivers and grows quite rapidly in Pekanbaru. This Study was purpose to analyze financial feasibility of InDriver drivers in Pekanbaru. The analytical method that used are BEP, PBP, IRR, NPV, and BCR. The averages results obtained from all five feasibility test for scenario 1 (main occupation) are BEP Rp. 110.000. PBP obtained is 2 years 7 month. IRR obtained is 6,52 %. NPV obtained is 41.845.193 and BCR obtained is 1,209. Meanwhile for the averages results obtained from all five feasibility test for scenario 2 (side occupation) are BEP Rp.99.600. PBP obtained is 3 years 0 month. IRR obtained is 6,8 %. NPV obtained is 6.634.452 and BCR obtained is 1,102. Based on the results of these five feasibility analytical methods, scenario 1 (main occupation) is feasible and scenario 2 (side occupation) of InDriver driver is not feasible based on UMK (City Minimum Wages).